2005
DOI: 10.1016/j.seizure.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizures, epilepsy and epileptic syndromes in newborns: A nosological approach to 94 new cases by the 2001 proposed diagnostic scheme for people with epileptic seizures and with epilepsy

Abstract: Compared to the 1989 ILAE classification, which allowed a syndromic diagnosis in only 6/94 patients, the remaining being classified as Epilepsies and Syndromes undetermined whether focal or generalized, the 2001 ILAE diagnostic scheme, applied at the end of the neonatal period, offers a variety of approaches to classification, allowing an early distinction between epilepsy and single or isolated clusters of seizures, with therapeutic and prognostic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
2
18
2
Order By: Relevance
“…In the studies that applied the ILAE classification of epileptic syndromes [21,55], authors reported a high prevalence of severe epilepsies, following neonatal seizures. Watanabe and collaborators have studied the outcome of newborns that presented epileptic syndromes, 41% of the infants that had neonatal symptomatic epilepsies developed West syndrome [46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies that applied the ILAE classification of epileptic syndromes [21,55], authors reported a high prevalence of severe epilepsies, following neonatal seizures. Watanabe and collaborators have studied the outcome of newborns that presented epileptic syndromes, 41% of the infants that had neonatal symptomatic epilepsies developed West syndrome [46].…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive classification of seizures occurring during the neonatal period among epileptic syndromes has improved with ILAE 2001 proposal [55]. Despite all the criticism that this classification brings with misdiagnosis, its recognition based on clinical criteria (Volpe classification) is widely used even in recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, CNS infection as etiology was found in 3-20%. 7,9,16,20,21 Among the 35 neonates with CNS Infection, 33 had distinctive pattern of white matter involvement with extension into the subcortical white matter, corpus callosum, optic radiation or tracts suggestive of parechoviral encephalitis. This pattern had to be distinguished from MRI abnormality due to other viral etiology like HSV, as HSV encephalitis involve both white matter and grey matter.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,16,20,21 Intra-parenchymal bleed was the commonest and is a well-known cause for neonatal seizures. IVH was observed in 3% of infants presenting with neonatal seizures and may be an incidental finding.…”
Section: Discussionmentioning
confidence: 99%